Evaluation of the effect of feruloyl esterase-producing Lactobacillus plantarum and cellulase pretreatments on lignocellulosic degradation and cellulose conversion of co-ensiled corn stalk and potato pulp. (August 2020) - Xu, Dongmei; Ding, Zitong; Bai, Jie; Ke, Wencan; Zhang, Yixin; Li, Fuhou; Guo, Xusheng
Highlights: Corn stalk and potato pulp were co-ensiled with a FEA strain A1 or cellulase. Use strain L. plantarum A1 alone in co-ensiling was not effective in enzymolysis. Cellulase plus strain A1 was well performed in fibre degradation during ensiling. Co-ensiled mixture without additives was well performed in enzymatic hydrolysis. Abstract: The effects of feruloyl esterase-producing Lactobacillus plantarum A1, cellulase, or their combination on the fermentation characteristics, carbohydrate composition, and enzymatic hydrolysis of mixed corn stalk and potato pulp silage were investigated. Two mixture ratios were used: a weight ratio of rehydrated corn stalk to potato pulp of 35:1 (HD) and a weight ratio of dry corn stalk to potato pulp of 5:11 (LD). No advantage was observed with the addition of strain A1 alone for lignocellulosic degradation and cellulose conversion, while its combination with cellulase enhanced the lignocellulosic degradation and preserved more fermentable carbohydrates in co-ensiled corn stalk and potato pulp. The enzymatic hydrolysis results indicated a potential benefit of pretreatment for biogas production, as the co-ensiled HD ratio mixture without additive treatment showed high glucose yield after enzymatic hydrolysis following 60 d of fermentation.